Deciphering the transcriptomic and lncRNA landscape of gilthead sea bream (Sparus aurata) in response to Photobacterium damselae subsp. piscicida infection - Pereiro, Patricia; Figueras, Antonio; Novoa, Beatriz (Frontiers in Marine Science, 2025)
IntroductionThe gilthead sea bream (Sparus aurata) is a key species in European aquaculture, but its production is threatened by infectious diseases, including photobacteriosis caused by Photobacterium damselae subsp. piscicida (Phdp). This bacterial pathogen leads to high mortality, particularly in larvae and juveniles, and poses a significant challenge due to rising antibiotic resistance and the limited efficacy of vaccines in early developmental stages. Despite extensive research into Phdp virulence factors, the immune mechanisms in gilthead sea bream remain poorly understood.MethodsIn this study, we conducted the first RNA-Seq analysis of Phdp-infected gilthead sea bream to characterize the immune response at 24 hours post-infection (hpi). We examined the expression of both coding genes and long non-coding RNAs (lncRNAs) in the head kidney and intestine.ResultsOur findings revealed a robust immune response, particularly in the head kidney, characterized by significant modulation of genes involved in complement and coagulation cascades, iron metabolism, pathogen recognition, antigen presentation, inflammation and reactive oxygen species (ROS) production and detoxification, among others.DiscussionThese results provide novel insights into the complex immune response of gilthead sea bream to Phdp and highlight the potential involvement of lncRNAs in modulating immune pathways. This lays the foundation for future research on host-pathogen interactions, which could support the development of preventive and control strategies for disease management, such as selective breeding for disease resistance, vaccine development, or host-derived alternatives to antibiotics.